All‐In‐One Dendrimer‐Based Lipid Nanoparticles Enable Precise HDR‐Mediated Gene Editing In Vivo. Issue 30 (17th June 2021) - Farbiak, Lukas; Cheng, Qiang; Wei, Tuo; Álvarez‐Benedicto, Ester; Johnson, Lindsay T.; Lee, Sang; Siegwart, Daniel J.
Abstract: Clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated (Cas) protein gene editing is poised to transform the treatment of genetic diseases. However, limited progress has been made toward precise editing of DNA via homology‐directed repair (HDR) that requires careful orchestration of complex steps. Herein, dendrimer‐based lipid nanoparticles (dLNPs) are engineered to co‐encapsulate and deliver multiple components for in vivo HDR correction. BFP/GFP switchable HEK293 cells with a single Y66H amino acid mutation are employed to assess HDR‐mediated gene editing following simultaneous, one‐pot delivery of Cas9 mRNA, single‐guide RNA, and donor DNA. Molar ratios of individual LNP components and weight ratios of the three nucleic acids are systematically optimized to increase HDR efficiency. Using flow cytometry, fluorescence imaging, and DNA sequencing to quantify editing, optimized 4A3‐SC8 dLNPs edit >91% of all cells with 56% HDR efficiency in vitro and >20% HDR efficiency in xenograft tumors in vivo. Due to the all‐in‐one simplicity and high efficacy, the developed dLNPs offer a promising route toward the gene correction of disease‐causing mutations. Abstract : A non‐viral, lipid nanoparticle (dLNP) delivery platform capable of co‐encapsulating and delivering Cas9 mRNA, sgRNA, and an ssDNA template is developed for homology‐directed repair (HDR)‐mediated gene correction of DNA mutations in vivo. The relative ratios of lipids and nucleic acids are systematically optimized to induce high HDR efficiency, thereby guiding potential treatment opportunities for correction of mutations that cause disease.